Hyperoside Protects Human Umbilical Vein Endothelial Cells Against Anticardiolipin Antibody-Induced Injury by Activating Autophagy - Wei, Aiwu; Xiao, Huidongzi; Xu, Guangli; Yu, Xile; Guo, Jingjing; Jing, Zhuqing; Shi, Shaoqi; Song, Yanli (Frontiers in Pharmacology, 2020)
Anticardiolipin antibody (aCL), an important characterization of antiphospholipid syndrome, shows an intense association with vascular endothelial injury. Hyperoside is a flavonoid extracted from medicinal plants traditionally used in Chinese medicines, displaying anti-inflammatory, anti-cancer, and anti-oxidative properties in various diseases. Recent studies have shifted the focus on the protective effects of hyperoside on vascular endothelial injury. However, little is known about the mechanisms involved. In the present study, we investigated the effect of hyperoside on aCL-induced injury of human umbilical vein endothelial cells (HUVECs) in vitro. Our data illustrated that aCL induced HUVEC injury via inhibiting autophagy. Hyperoside reduced aCL-induced secretion of proinflammatory cytokines IL-1β and IL-8 and endothelial adhesion cytokines TF, ICAM1 and VCAM1 in HUVECs. Additionally, hyperoside activated autophagy and suppressed the mTOR/S6K and TLR4/Myd88/NF-κB signaling transduction pathways in aCL-induced HUVECs. To the best of our knowledge, this is the first study to investigate the effect of hyperoside on aCL-induced injury, as well as offer insights into the involved mechanisms, which is of great significance for the treatment of antiphospholipid syndrome.